Umetna inteligenca in prihodnost odvetniškega poklica - Premelč, David (Podjetje in delo, 2023)
The paper discusses the extremely rapid development of artificial intelligence systems and analyses their impact and applicability in the provision of legal services both on a global level and in Slovenia. In doing so, it attempts to define how recent and future technological developments in the field of AI will affect the legal profession itself, in particular the structure of work and employees in law firms, and what adjustments and restructuring can therefore realistically be expected in the short and medium term. On the one hand, it highlights a number of ethical, legal and regulatory dilemmas associated with the use of AI systems, including in terms of possible interference with individual rights. On the other hand, it highlights such dilemmas, especially against the background of the existing normative regulation of the legal profession in Slovenia, including the issues of liability, the duty of confidentiality and the need for adequate regulation of the services of alternative providers of legal advice using AI.
Keywords: odgovornost; odvetniki; odvetniške storitve; odvetništvo; regulatorni okvir; Sodišča; umetna inteligenca; zaupnost